Educational disadvantages in single fatherhood and single motherhood family pathways - Klara Capkova; Marika Jalovaara (Stockholm University Demography Unit, 2022)
Previous research on single parenthood is predominantly concerned about socio-economic disadvantages associated with single motherhood. Much less is known about single fatherhood and how it is linked with socioeconomic disadvantage. Using register data on Finnish cohorts born in 1969-70, and employing sequence and cluster methods, we take a longitudinal life-course approach to family trajectories that involve single parenthood. We identify the most typical family life courses of single fathers and mothers, and study whether single fatherhood and motherhood are similarly linked to educational disadvantage. The results show that compared to single mothers, single fathers’ family life courses are more turbulent and more often involve spells of non-resident parenthood. For both single fathers and mothers, the largest disadvantage is associated with long spells of non-resident parenthood, and pathways with early family formation. Whereas educationally advantageous pathways of single fathers are characterized by postponed family formation, for single mothers the advantage is linked to single parenthood placed at higher ages in the family trajectory, regardless of the timing of first birth. We situate single parenthood within the family dynamics of contemporary Finland, a social and gender egalitarian welfare state, and show that even though fathers and mothers are in principle enabled to take the main responsibility for childcare, in practice, notable gender differences prevail